Growth hormone deficiency due to traumatic brain injury in a patient with X-linked congenital adrenal hypoplasia - Engiz, Ozlem; Ozön, Alev; Riepe, Felix; Alikaşifoğlu, Ayfer; Gönç, Nazli; Kandemir, Nurgün (The Turkish Journal of Pediatrics, 2010)
X-linked adrenal hypoplasia congenita (AHC) is characterized by primary adrenal insufficiency and is frequently associated with hypogonadotropic hypogonadism (HH). The production of other pituitary hormones (adrenocorticotropic hormone [ACTH], growth hormone [GH], thyroid-stimulating hormone [TSH], and prolactin [PRL]) is usually normal. Mutations of the DAX-1 gene have been reported in patients with AHC and HH. We present a 13-year-old male patient with AHC caused by a nonsense mutation in the DAX-1 gene who developed GH deficiency following head trauma. He showed signs of adrenal insufficiency at the age of 23 months, and glucocorticoid and mineralocorticoid treatment was started. His parents reported head trauma due to a traffic accident at the age of 21 months. Adrenal computed tomography revealed hypoplasia of the left and agenesis of the right adrenal gland. Decreased growth rate was noted at the age of 12.5 years while receiving hydrocortisone 15 mg/m2/day. His height was 139.9 cm (-1.46 SD), body weight was 54.9 kg, pubic hair was Tanner stage 1, and testis size was 3 ml. His bone age was 7 years. His gonadotropin (follicle-stimulating hormone [FSH], luteinizing hormone [LH]) and testosterone levels were prepubertal. The evaluation of GH/insulin-like growth factor-1 (IGF-1) secretion at the age of 13 years revealed GH deficiency. Pituitary magnetic resonance imaging demonstrated a hypoplastic hypophysis (< 2.5 mm) and a normal infundibulum. GH treatment (0.73 IU/kg/week) was started. This paper reports a patient with genetically confirmed AHC demonstrating GH deficiency possibly due to a previous head trauma. Complete pituitary evaluation should be performed in any child who has survived severe traumatic brain injury.